Breakage of tapered junctions of modular stems in revision total hip arthroplasty: high incidence in a consecutive series of a single snstitution - Bischel, Oliver E.; Höppchen, Arnold; Böhm, Paul M.; Bormann, Therese; Jäger, Sebastian; Seeger, Jörn Bengt (Bioengineering, 2023)
Background: Modularity in revision THA (RTHA) has become accepted during the last three decades. Nevertheless, specific risks of modularity of current revision devices such as breakage of taper junctions occur during follow-up. Data reporting failure rates are predominantly given by the manufacturers but independent data acquisition is missing so far. Questions/Purposes: 1. What time-related risk of breakage of taper junction between neck and body of an established modular revision device can be expected in a consecutive single institutional series and a mid-term follow-up? 2. Are there specific factors influencing breakage in this cohort? Materials and Methods: A retrospective analysis was performed of a consecutive series of 89 cases after femoral revision using a tapered modular revision stem. Mean follow-up period was 7.1 (range: 3.0-13.7) years. Breakage of stem as failure criteria of the implant was investigated with a Kaplan-Meier analysis. Results: Breakage of taper junctions occurred in four patients during follow-up showing a time-depending implant survival of 94.2 (95% CI: 88.6-100%) after 13.7 years. Implant survival of stems with lateralized necks of 87.4 (95% CI: 75.6-100%) after 13.7 years was significantly lower compared to the standard offset variant with 100% after 13.5 years (log rank test p = 0.0283). Chi square test also revealed a significantly higher risk of breakage of lateralized necks compared to standard offset pieces (p = 0.0141). Three of four patients were obese with a mean BMI of 37.9 kg/m2. Grade of obesity (grade 1 or higher) had significant influence on risk of breakage. Survival of the implant was significantly lower in obese patients with at least grade 1 obesity compared to patients with a BMI < 30 kg/m2 (82.9 (95% CI: 64.9-100%) after 11.6 years vs. 98.4 (95% CI: 95.3-100%) after 13.7 years; log-rank p = 0.0327). Conclusions: Cumulative risk for failure of taper junctions was high in this consecutive single institutional cohort and may further increase during follow-up. As independent data acquisition in registries is missing, failure rate may be higher than reported data of the manufacturers. The use of lateralized offset necks in obese patients of at least grade 1 obesity showed a significantly higher risk of breakage. The use of monobloc revision devices may be an option, but randomized control trials are currently missing to establish standardized treatment protocols considering individual risks for both monobloc and/or modular implants.
Gesehen am 26.05.2023